Laminoplasty vs laminectomy in the surgical management of spinal intradural extramedullary tumors - Deepak Kumar Singh; Prevesh Kumar Sharma; Vipin Kumar Chand; Kaif Mohammad; Kuldeep Yadav; Neha Singh (Egyptian Journal of Neurosurgery)
Abstract Background Laminectomy and laminoplasty have been widely used for patients with spinal cord tumors. Spinal tumors comprise around 5–10% of all central nervous tumors, with 70–80% of these being intradural extramedullary in location. Surgery is the main treatment modality for spinal tumors. In this case series, we aimed to compare the laminectomy and laminoplasty procedure in the surgical management of intradural extramedullary spinal tumors and analyze the advantages and disadvantages of both the procedures. Materials and method The clinical and radiological data of patients who underwent laminectomy or laminoplasty for spinal cord tumors were retrospectively analyzed. Out of the 56 patients undergoing surgery for spinal IDEM, “En-bloc osteoplastic laminoplasty” with titanium microplates was performed in 26 patients, while 26 patients had laminectomy without disrupting the facet joints, and 4 patients required fusion with screws and rods along with laminectomy. All these patients were followed for one year. Patient data, including surgical time, blood loss, length of hospital stay, post-operative complications, post-operative neurological status, post-operative pain, and preoperative and post-operative deformity, were gathered and analyzed in both the laminectomy and laminoplasty groups. Results Of the total, there were 23 males and 33 females, with a mean age of 39.47 ± 13.65 years in the laminectomy group and 37.23 ± 12.03 in the laminoplasty group. The average operative time for laminectomy procedures was 138.86 ± 10.90 min, while it was 145.19 ± 9.54 in the laminoplasty group. The average length of hospital stay in the laminectomy group was 6.50 ± 2.01 days, and 5.08 ± 1.47 days in the laminoplasty group. The mean blood loss in laminectomy group was 118 ± 15.05 ml, whereas in laminoplasty group the mean blood loss was around 110 ± 12.46 ml. Also, laminoplasty group had a lower incidence of post-operative deformity. Conclusions Laminoplasty is a constructive technique in the management of intradural extramedullary spinal tumors, associated with fewer post-operative complications, lower incidence of new post-operative deformities or worsening of preoperative deformities, and a shorter duration of post-operative pain. Additionally, it alleviates the need for additional instrumentation, thereby avoiding an extra financial burden while enhancing the quality of life for the patient. A high-quality randomized controlled trial with long-term follow-up is necessary to validate the findings of this innovative technique.